SISTEM PENDUKUNG KEPUTUSAN SELEKSI PENERIMA BEASISWA PADA POLITEKNIK KRAKATAU DENGAN MENGGUNAKAN METODE SIMPLE ADDITIVE WEIGHTING (SAW) - Muhamad Effendi; Shodik Nuryadhin; Teuku Fadjar Shadek (JURNAL SATYA INFORMATIKA, 2022)
Scholarships are a work program that exists in every school. The scholarship program is held to ease the burden on students in pursuing their study period, especially in terms of costs. Krakatau Polytechnic is an educational institution that already has a scholarship program for students. Therefore scholarships must be awarded to deserving and deserving recipients of them.To assist in determining students who are eligible to receive scholarships, a decision support system is needed. In the process of developing a decision support system for determining scholarship recipients at the Krakatau Polytechnic using the Simple Additive Weighting (SAW) method. This method was chosen because it is able to select the best alternative from a number of alternatives, in this case the intended alternative is those who are entitled to receive scholarships based on predetermined criteria. The research was conducted by looking for weight values for each attribute, then a ranking process was carried out which would determine the optimal alternative, namely the best achieving students who deserved to receive scholarships